Understanding the Resistive Switching Phenomena of Stacked Al/Al2O3/Al Thin Films from the Dynamics of Conductive Filaments. (20th September 2017) - Molina-Reyes, Joel; Hernandez-Martinez, Luis
Abstract : We present the resistive switching characteristics of Metal-Insulator-Metal (MIM) devices based on amorphous Al2 O3 which is deposited by Atomic Layer Deposition (ALD). A maximum processing temperature for this memory device is 300°C, making it ideal for Back-End-of-Line (BEOL) processing. Although some variations in the forming, set, and reset voltages (V F O R M, V S E T, and V R E S E T ) are obtained for many of the measured MIM devices (mainly due to roughness variations of the MIM interfaces as observed after atomic-force microscopy analysis), the memristor effect has been obtained after cyclic I - V measurements. These resistive transitions in the metal oxide occur for both bipolar and unipolar conditions, while the I O F F / I O N ratio is around 4–6 orders of magnitude and is formed at gate voltages of V g < 4 V. In unipolar mode, a gradual reduction in V S E T is observed and is related to combined (a) incomplete dissolution of conductive filaments (made of oxygen vacancies and metal ions) which leaves some residuals and (b) thickening of chemically reduced Al2 O3 during localized Joule heating. This is important because, by analyzing the macroscopic resistive switching behavior of this MIM structure, we could indirectly relate it to microscopic and/or nanoscopic phenomena responsible for the physical mechanism upon which most of these devices operate.